Use of diallel matings to estimate maternal effects and general and specific combining abilities in swine - J D Wheat; T Yu; R R Schalles (Kansas Agricultural Experiment Station Research Reports, 1970)
As early as 1926, Danish workers reported that cross-breeding gave larger litters at weaning that gained faster on less feed per pound of gain. Crossbreeding is now used extensively in market hog production. It uses heterosis that results from hybrid combinations. Heterosis (superiority of crossbred progeny over the average of their parents) may be evaluated in terms of a high general combining ability, the capacity to cross well in several crosses, and specific combining ability, the ability to "nick" or cross particularly well with certain other strains, but not with all. Strains that "nick" well are said to have specific combining ability.; Swine Day, Manhattan, KS, October 1, 1970
Keywords: Swine day; 1970; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 163; Swine; Diallel matings; Maternal effects